Evaluation of lipid profile and its relationship with blood pressure in patients with Cushing's disease. Issue 5 (May 2018) - Qin, Lang; Zhu, Xiaoming; Liu, Xiaoxia; Zeng, Meifang; Tao, Ran; Zhuang, Yan; Zhou, Yiting; Zhang, Zhaoyun; Yang, Yehong; Li, Yiming; Wang, Yongfei; Ye, Hongying
Abstract : Introduction: The purpose of the study was to describe lipid profile and explore pathogenetic role of LDL-c on hypertension in patients with Cushing's disease (CD). Hypertension is a common feature in patients with CD. Previous study found low-density lipoprotein cholesterol (LDL-c) uptake in vascular cells might be involved in vascular remodeling in patients with CD. Therefore, we evaluated the relationship between lipid profile and the blood pressure in patients with CD. Methods: This retrospective study included 84 patients referred to Huashan Hospital for the evaluation and diagnosis of CD from January 2012 to December 2013. All subjects had detailed clinical evaluation by the same group of endocrinology specialists to avoid subjective influences. Results: We found that high LDL-c patients had significant higher body mass index (BMI), systolic blood pressure (SBP), cholesterol (CHO), triglyceride (TG), and apolipoproteinB (apoB) ( P < 0.05). An association was detected between SBP values and lipids profile including CHO, TG, LDL-c, apolipoproteinA (apoA), apoB and lipoprotein(a) (LP(a)). After adjustment for all covariates, the LDL-c remained positively associated with SBP. In patients with or without taking statins, patients with LDL-c ≥3.37 mmol/L had higher SBP than patients with LDL-c <3.37 mmol/L. Then, LDL-c was coded using restricted cubic splines (RCS) function with three knots located at the 5th, 50th and 95th percentiles of the distribution of LDL-c. Compared to individuals with 3.215 mmol/L of LDL-c, individuals with 4.0, 4.5 and 5.0 mmol/L of LDL-c had differences of 3.86, 8.53 and 14.11 mmHg in SBP, respectively. Conclusions: An independent association between LDL-c and SBP was found in patients with CD. We speculate that LDL-c may be a pathogenic factor for hypertension in those patients.